The Most Common Complications of Celiac Disease and the Impact of a Gluten-Free Diet on Their Course - Kosucka, Wiktoria; Wiśniewska, Aleksandra; Kaszyńska, Karolina; Dąbek, Jakub; Balik, Dominik; Kwaśniewska, Anna; Lara, Joanna; Kubicka, Jagoda; Grabowska, Martyna; Grabowska, Karolina (Quality in Sport, 2025)
Celiac disease is a gluten-sensitive, immune-mediated enteropathy that occurs in people with a genetic predisposition and leads to inflammation in the small intestine. During its course, characteristic antibodies are produced, which together with histopathological examination of material taken from the intestine, are the main elements of the diagnostic process. Depending on the symptoms present and microscopic changes, we distinguish classical, non-classical, subclinical and potential forms. The most typical presentation, in the form of gastrointestinal symptoms includes diarrhea, abdominal pain and weight disturbances. Atypical symptom, which may involve multiple other systems, are also increasingly observed. The cornerstone of treatment is a lifelong gluten-free diet that excludes all products containing wheat, barley and rye. In most cases, it helps alleviate or resolve symptoms and regenerate the intestinal mucosa. The long diagnostic process, non-adherence to the diet and resistance to treatment pose a high risk of complications at various stages of the disease, so it is important for the patient to cooperate appropriately with the doctor and nutritionist. The purpose of this paper is to review the most common complications of celiac disease and evaluate the impact of an appropriate diet on their course.